Rationality and irrationality in the use of antibiotics in the epiclatino Latin American Neonatal Units - B Hoyos, Angela (Journal of Advanced Pediatrics and Child Health, 2021)
Background: Recent years have seen chaos in the neonatology use of antibiotics with diverse opinions and recommendations in international guidelines and societies. This has created great uncertainty in which cases to use, for how long, and which tests apply to make these decisions. We conducted a retrospective cohort study about the use of antibiotics in the EpicLatino neonatal units and a Latin American network database, after noting these variations in the 2019 report. Methods: For the year 2019 using the EpicLatino database, we included cases (only first admission) ≤ 32 weeks gestational age at birth, excluding one unit that did not accept to participate. The number of cases and days receiving antibiotics were recorded as well as the progression for each unit. Inappropriate use of antibiotics was defined as greater than 3 days in patients with negative cultures (blood/CSF cultures) excluding: major malformations, urinary tract infections, necrotizing enterocolitis (NEC) and cases with suspected chorioamnionitis in the mother (the latter two only during the course of diagnosis of NEC or chorioamnionitis). Results: A total of 6,543 days of antibiotics were observed, 49.5% of cases had at least one positive blood/CSF culture. A total of 595 days of antibiotics without justification were found in 72 courses in 61 cases: 19.4% had no diagnosis of infection in the database, 9.7% did not document any culture throughout their stay, and 51,4% obtained only one blood/CSF culture during their entire stay. In the 58 cases with diagnosis of infection: 41% were clinical sepsis and a diagnosis of pneumonia with a poor positive culture correlation was found. Furthermore, 74% of the unit’s didn´t use pneumonia as a justification to use antibiotics. Other diagnosis found: Conjunctivitis, NEC 1A and rotavirus NEC. Conclusion: Although the method of reviewing the use of antibiotics in a database has a number of limitations, especially the cause that motivated the use of antibiotics and other tools used for diagnosis of infections, the notable differences between units is striking. Although it is difficult to make recommendations to all units, it is important to control infections in some units and in others to reduce the excessive use of antibiotics, especially with diagnosis of pneumonia in neonates and negative blood/CSF cultures.